Experimental Investigation on the Physical, Microstructural, and Mechanical Properties of Hemp Limecrete - Saavedra-Flores, E (Nature Research, 2023)
This paper investigates the hemp limecrete mechanical and microstructural performance of a new sustainable and environmental friendly building material. Several studies have investigated the hemp limecrete focusing on the non-structural applications. The newly developed hemp limecrete consists of high mechanical and microstructural properties. The specimens were prepared with varying lengths and proportions of hemp fibers with lime and tested for compressive strength, flexural strength, thermal conductivity and microstructural analysis like SEM and EDS. The study found that the optimal fiber content for making mortars was between 2 and 4%. This conclusion was reached after analyzing the influence of fiber length and ratio on the properties of the mortars. The dry unit weight decreased when the fiber content was higher than 4%. In terms of strength, the study found that the flexural strength of the hemp limecrete improved with an increase in fiber ratio, but the compressive strength decreased. However, with 2% hemp fiber, compressive strengths of 3.48 MPa and above were obtained. The study also highlighted the good thermal insulation properties and dimensional stability of hemp limecrete. These findings have important implications for the use of hemp limecrete as a sustainable building material. The results suggest that hemp limecrete has the potential to be a viable alternative to conventional concrete in specific applications, particularly in areas where environmental sustainability is a priority. © 2023, The Author(s).